An investigation into the factors to affect capital structure: Empirical evidence from China’s listed travel corporations - Qian, Cheng (2010)
The modern capital structure theories indicate that the capital structure is closely correlated with the corporate governance and corporate performance. Thus a large number of scholars attempted to investigate the determinants of the capital structure. As most previous studies point out that the industrial factors have significant influence on the capital structure, this research will focus on studying the determinants about the capital structure of China’s listed travel enterprises. In general, this research aims to analyze the following questions. (1) How do I choose the appropriate indicators to reflect the factors to affect the capital structure of China’s listed travel corporations? (2) How will I evaluate the capital structure of China’s listed travel corporations? (3) How will the factors affect the capital structure of China’s listed travel corporations?